Assessing the Risk of Hypertensive Nephropathy in the Elderly: A Critical Examination of a Silent Threat - Treesia Sujana; Widyadari Prasetyaningrum (CV Media Inti Teknologi, 2026)
Background: Hypertension has been a prevalent condition among the elderly within the community, often receiving insufficient attention from those affected. Based on screening data, it was found that 52.63% of the 57 elderly people in Awiligar had blood pressure in the hypertension category. This high prevalence indicates that this population is at high risk for cardiovascular and kidney complications.Objectives: This community service initiative seeks to facilitate the early detection of cardio-renal risk among the elderly population in Awiligar, Bandung Regency, in light of the high prevalence of hypertension and the potential for chronic kidney complications.Methods: The method for implementing this community service activity consists of Health Screening and Health Education.Result: The screening results revealed a high prevalence of hypertension, with 52.63% of participants exhibiting BP ≥ 140/90 mmHg. Urine laboratory findings indicated significant abnormalities, notably Proteinuria in 42.11% (24 individuals) and Hematuria in 21.05% (12 individuals). Furthermore, a high prevalence of metabolic risk indicators was observed. The elevated prevalence of proteinuria, in conjunction with the high incidence of hypertension, serves as a significant marker of early kidney damage within this population.Conclusion: The conclusion of this initiative underscores the necessity for immediate medical follow-up and community-based health education interventions aimed at managing cardio-renal risk factors to prevent the progression of Chronic Kidney Disease.